Affective Symptoms and Traumatic Stress Among College Students at Risk for ADHD During the Second Lockdown in Greece - Koutra, Kleio; Kokaliari, Effrosyni (European Journal of Mental Health, 2022)
Introduction: Due to the pandemic, individuals with ADHD have been facing noticeable challenges in their daily life. Prolonged quarantine and isolation may contribute to higher affective and PTSD symptoms among college students with ADHD.Aims: The study aimed to explore the impact of COVID-19 on affective symptoms such as depression, anxiety, stress, along with loneliness and post-traumatic stress on college students at risk for ADHD in Greece during the second COVID-19 lockdown in November 2020.Methods: A sample of 362 students completed an online survey consisting of demographic questions and four instruments: the ADHD Self-Report Scale-V1.1 (ASRS-V1.1), the DASS-21, the UCLA Loneliness Scale, and the PTSD checklist (PCL-5).Results: Over 18% of the students met the criteria for being at risk of ADHD, which is higher than in other studies conducted prior to the pan-demic. Students at risk for ADHD reported significantly higher (p < .05) mean scores on all scales: depression, anxiety, stress, loneliness, and post-traumatic stress. A model to predict at-risk ADHD diagnosis indicated those who presented symptoms of depression, had low GPA, who were employed, were 46% more likely to struggle with ADHD.Conclusions: This study indicates that the pandemic may have adversely affected individuals at risk for ADHD. Recommendations for further re¬search and implications for mental health professionals are discussed.